Laboratory testing of the Monotonic behavior of partially saturated sandy soil - Della Noureddine (Earth Sciences Research Journal, 2010)
This paper presents a laboratory study on the influence of the saturation evaluated in term of Skempton's pore pressur coefficientBon the behavior of Chlef sand. The study is based on drained and unnonno drained compression tests which were carried out for Skempton's pore pressure coefficient varying between 13 and 90%.The tests were conducted on medium dense sand samples having an initial relative density Id = 0.50 at an effective stress of 100 kPa. The paper is composed of two parts. The first one presents the characteristics of the sand used in this study. The second provides an analysis of the experimental results and discusses the influence of Skempton's pore pressure coefficient (B) on the mechanical characteristics of the sand. The tests show that the increase in the Skempton' S pore pressure coefficient (B) reduces the soil dilatancy and amplifies the phase of contractancy and reduces the frictional and characteristic angle of the sand. The residual strength decreases with the increase ininin the Skempton's pore pressure coefficient B.